A estruturação da operação de logística reversa no contexto de resíduos sólidos pós-consumo de produtos do segmento eletroeletrônicos de uso doméstico no Brasil - Alós, Jandir dos Santos (Universidade do Vale do Rio dos Sinos, 2021)
We live in a world in evolution, with changes that allow us, in the short term, satisfaction, comfort and well-being, especially with the use of technologies, enjoyed through electronic devices. However, to maintain this lifestyle, it is necessary to remember that we consume more and more. Studies indicate a projection of an increase in solid waste generation of around 70% by 2050. Therefore, it is necessary to create a sustainable economic system. In this context, the PNRS – National Solid Waste Policy represents a milestone for Brazilian society regarding the environmental issue, especially with the approval of Decree No. 10.240 / 20, with an emphasis on an advanced view on how to treat solid waste consumer electronics segment in Brazil. Therefore, the general objective of this research is to present a framework aimed at structuring the operation of the Reverse Logistics System in the context of post-consumer solid waste of products in the household electrical and electronics segment in Brazil. In this sense, it was implemented an exploratory research, qualitative in nature, operationalized through individual in-depth interviews with a semi-structured approach, with fourteen respondents, added to documentary research, from access to documents and information related to the research context. For data analysis, the technique of content analysis was used, with the support of a qualitative data analysis software, NVivo. To validate the contents and, more specifically, the proposed framework, data triangulation was performed, through the operation of two focus groups, with seven of the fourteen participants who had already been interviewed. The data and information collected, as well as the theoretical framework accessed, suggest that structural difficulties such as the installation of 5,000 points for receiving WEEE - Waste Electrical and Electronic Equipment, the lack of consumer engagement and the form of communication of the SLR - Reverse Logistics System, are major challenges that need to be faced, so that the goals defined in Decree No. 10.240/20 are achieved. The cost for the operation of this structure must also be treated as a critical point for the success of this system, mainly due to the lack of a vision focused on the circular economy, the lack of incentives from the public authorities and the difficulty of inspecting importers of EEE - Electrical Equipment and Electronics, ensuring the isonomy of the process. To enhance this SLR, the use of technologies, consumer incentives as well as the establishment of public-private partnerships will be indispensable.
Keywords: Gestão de operações; Logística reversa; Resíduos pós-consumo; Resíduos de equipamentos eletroeletrônicos pós-consumo; Redução de resíduos; Sustentabilidade; Operations management; Reverse logistics; Post-consumer electronic equipment waste; Waste post-consumer; Waste reduction; Sustainability; ACCNPQ::Ciências Sociais Aplicadas::Administração